Development of a "Virtual Learning Factory" for learning and applying specific Lean manufacturing methods. Issue 1 (1st March 2022) - Neacsu, G C; Pascu, I G; Nitu, E L; Ionescu, L; Gavriluta, A C; Belu, N
Abstract: The processes and systems of production and training, influenced by the digital era, are forced to evolve at an accelerated pace to satisfy the need of innovation and digitization. Thus, the development of virtual learning factories within universities, which can adapt to the requirements of innovation and digitalization, is a solution. In this context, the paper presents how to development a virtual learning factory, flexible-reconfigurable to allow easier learning and experimentation of methods, techniques and tools used in Lean manufacturing. To achieve this, specific Lean manufacturing methods will be digitized for integration into the virtual factory, through programming in the Unity platform, using its specific C # language. Thus, at the end of the paper we want to obtain a virtual, mobile and flexible learning factory, which will help the user to understand, learn and experiment easily and in an attractive way the methods and techniques used in Lean manufacturing.